DISTRIBUTION OF INDIAN FLYING FOX PTEROPUS GIGANTEUS BRÜNNICH, 1782 IN FOUR DISTRICTS OF KHYBER PAKHTUNKHWA - M. Salim; M. Mahmood-ul-Hassan (Journal of Animal and Plant Sciences, 2015)
The Indian flying fox Pteropus giganteus (Brünnich, 1782) is Indomalayan in distribution. Present study documents its range extension towards west of the Indus in Pakistan. Five colonies of the Indian flying foxes were recorded in four districts of Khyber Pakhtunkhwa (KP) that form eastern boundary of Palaearctic region. The bats preferred to roost on Populus nigra (100%), Eucalyptus globulus (88.8%), Dalbergia sisso (76.0%) and Platanus orientalis (48.4%). Population size varied from June (n = 5478) to December (n = 912). from Peshawar and Charsadda districts (Mahmood-ul-
Keywords: Indo-Malayan; Indus; Khyber-Pakhtunkhwa; flying fox